Analysis of power losses in an industrial planetary speed reducer: Measurements and computational fluid dynamics calculations. (January 2014) - Concli, Franco; Conrado, Edoardo; Gorla, Carlo
In this work, experimental and theoretical analyses of the power losses in an industrial planetary speed reducer were performed in order to define the weight of the different types of power losses in the global efficiency as well as to understand the appropriateness and the effectiveness of the models and tools available in the literature for the prediction of these power losses. From this investigation, it has emerged that even if for all the kinds of power losses improvements are in principle possible, those for which, at the same time, more improvements seem possible and effective models are lacking are the load-independent power losses. For this reason, a computational fluid dynamics methodology able to evaluate load-independent gear power losses in planetary gearboxes is proposed. The other types of power losses were determined by means of analytical models available in the literature and, together with the calculated load-independent gear power losses, compared with the experimentally determined power losses showing the effectiveness of the adopted calculation models.